Perkembangan Sosial Emosional Anak Usia 5-6 Tahun Selama Pembelajaran Jarak Jauh Di Raudhatul Athfal - Restu Pujianti; Sumardi Sumardi; Sima Mulyadi (UIN Sultan Maulana Hasanuddin Banten, 2021)
Children’s social emotional development is the child’s achievement in adjusting to his environment and understanding his feelings when interacting with others. This emotional social development can develop one of which is through learning activities in schools where children learn various things and interact with many people, especially peers. There are three indicators of the achievement of social emotional development in early childhood, namely self-awareness, a sense of responsibility for oneself and others, and prosocial behavior. In this article, the author describe the social emotional development of children aged 5-6 years during distance learning at Raudhatul Athfal in Cipedes District, Tasikmalaya City. The research method used in this research is descriptive quantitative using a survey across sectional research desain, namely data collection is carried out at one time. Keywords: early childhood; social emotional; distance learning. References Age, J. G., & Hamzanwadi, U. (2020). Perilaku Sosial Emosional Anak Usia Dini. Jurnal Golden Age, 4(01), 181–190. https://doi.org/10.29408/jga.v4i01.2233. Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan dari Penangguhan Walimat Al- ‘Ursy Di Masa Darurat COVID-19 Melalui Sadd Adz-Dzari’ah. Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 27–38. Davies, P. D. O. (2002). Multi-drug resistant tuberculosis. CPD Infection, 3(1), 9–12. Desmita. (2013). Psikologi Perkembangan. PT. Remaja Rosdakarya. Dewi, AR., Mayasarokh, M., Gustiana, E. (2020). Perilaku Sosial Emosional Anak Usia Dini. 04 (1). 181-190. Eliningsih, E. (2021). Peningkatan Kemampuan Guru Dalam Manajemen Pengelolaan Kelas Di Masa Pandemi Covid-19 Melalui Supervisi Klinis Pengawas Di SDN 15 Perawang. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 6(1), 25–36. Hidayat, F., Hidayat, I., Ghofur, A., & Santoso, F. S. (2021). Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 11(1), 1–12. Ifadah, Y. K. (2019). Upaya Guru dalam Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini di TK Dharma Wanita Desa Totokan Kecamatan Mlarak Kabupaten Ponorogo. Institut Agama Islam Negeri Ponorogo. Ifadah, Y. K. (2019). Upaya Guru dalam Meningkatkan Perkembangan Sosial Emosional Anak Usia Dini di TK Dharma Wanita Desa Totokan Kecamatan Mlarak Kabupaten Ponorogo. Institut Agama Islam Negeri Ponorogo. Khaironi, M. (2018). Perkembangan Anak Usia Dini. 3 (1). 1-12. Lestari, R. H., & Alam, S. K. (2019). Analisis Keterlibatan Ayah dalam Mengembangkan Perkembangan Sosial Emosional Anak Usia Dini. 3(Juni), 1–8. Mastoah, I., & MS, Z. (2020). Kendala Orang Tua Dalam Mendampingi Anak Belajar Pada Masa Covid 19 Di Kota Serang. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2), 121–128. Nurhasanah, N. (2020). Pengaruh Pembelajaran Jarak Jauh Terhadap Keterampilan Sosial Anak Usia 5-6 Tahun. In Universitas Pendidikan Indonesia (Vol. 68, Nomor 1). Universitas Pendidikan Indonesia. Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 10(1), 1–12. Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 137 Tahun 2014 tentang Standar Nasional Pendidikan Anak Usia Dini. Sujiono, Y. N. (2016). Konsep Dasar Pendidikan Anak Usia Dini. PT. Indeks. Sujiono, YN. (2016). Konsep Dasar Pendidikan Anak Usia Dini. Jakarta: PT. Indeks. Surat Edaran Menteri Pendidikan dan Kebudayaan Nomor 15 Tahun 2020 Tentang Pedoman Penyelenggaraan Belajar dari Rumah dalam Masa Darurat Penyebaran Coronavirus Disease (COVID-19). Surat Edaran Nomor 4 Tahun 2020 Tentang Pelaksanaan Kebijakan Pendidikan dalam Masa Darurat Penyebaran Coronavirus Disease (COVID-19). Surur, A. M., & Nadhirin, A. U. (2020). Manajemen Waktu Pembelajaran Daring Di Masa Pandemi Covid-19 Pada TK Dharma Wanita 1 Baleturi. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2). Yusuf, S. (2011). Psikologi Perkembangan Anak & Remaja. PT. Remaja Rosdakarya.